2012
DOI: 10.1111/j.1582-4934.2011.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

A limited role for regulatory T cells in post‐ischemic neovascularization

Abstract: Recently, it was demonstrated that arteriogenesis is enhanced in mice deficient in regulatory T cells (CD4+CD25+FoxP3+ T cell), which can suppress effector T cell responses. The present study investigates the effects of these regulatory T cells on arteriogenesis in more detail by either specific expanding or depleting regulatory T cells. Hind limb ischemia was induced by electro-coagulation of the femoral artery in mice. Regulatory T cells were either expanded by injecting mice with a complex of interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In PCAF −/− mice, we demonstrated decreased numbers of circulating leukocytes involved in arteriogenesis, like T cells 46 (predominantly activated CD4 + T cells 7, 11 ), natural killer cells 11 and regulatory T cells 9, 10 , and also in those cells that have not previously been implicated in arteriogenesis, including B cells. Furthermore, fewer dendritic cells were found in draining inguinal lymph nodes compared to WT mice, where the interaction between antigen-presenting dendritic cells and T cells takes place.…”
Section: Discussionmentioning
confidence: 74%
“…In PCAF −/− mice, we demonstrated decreased numbers of circulating leukocytes involved in arteriogenesis, like T cells 46 (predominantly activated CD4 + T cells 7, 11 ), natural killer cells 11 and regulatory T cells 9, 10 , and also in those cells that have not previously been implicated in arteriogenesis, including B cells. Furthermore, fewer dendritic cells were found in draining inguinal lymph nodes compared to WT mice, where the interaction between antigen-presenting dendritic cells and T cells takes place.…”
Section: Discussionmentioning
confidence: 74%
“…Notably, several studies have indicated that type 1 T cells are more susceptible to Treg-mediated suppression than type 2 T lymphocytes [55]. However, Hellingman and coworkers recently reported only a mild inhibition of blood recovery in mice depleted of Tregs [56]. This suggests the possibility that augmented efficiency in blood flow recovery detected in CD28-deficient mice might be caused by intrinsic enhancement of type 1 responses.…”
Section: Reviewmentioning
confidence: 97%
“…Arteriogenesis is an inflammation-driven process [2], involving both the adaptive immune system (CD4 + T cells [3] [4], CD8 + T cells [5], regulatory T cells [6], [7]) and the innate immune system (monocytes [8][12], Toll-like receptors).…”
Section: Introductionmentioning
confidence: 99%